On Baltic Slovenia and Adriatic Lithuania : a qualitative comparative analysis of patterns in post-communist transformation - Norkus, Zenonas (Apostrofa, 2012)
A unique application of social science software to generate typology and ranklist of transition models of twenty-nine countries in Europe and Asia, ranging from Estonia to Vietnam, Norkus provides a highly innovative internationally comparative causal analysis of the variation in political and economic outcomes after the first decade of post-communist transformations, using multi-value Qualitative Comparative Analysis and Tosmana programme. The analysis includes a critical revision of received dichotomies (e.g. on gradualism versus "shock therapy"), and contributes to current debates on the varieties of post-communist capitalism